Internet security you can afford : using untangle as your internet gateway - Dawson, Christopher (Boston, MA : Cengage Learning, 2012)
Demonstrates how you can establish Internet security for free, or for very little money, using Untangle[registered] and buying only value-added components that you really need. This book serves as the reference tool for readers who understand end-user IT, hardware, and operating systems, but who have limited experience in network administration.
Part I: Questions. 1. Who should read this book? 2. But can't Norton(R) just do the job? 3. I can't just build an Internet gateway! Wait, what's an Internet gateway? 4. Can't I just pay someone to take care of all that Internet security stuff? 5. Free? What's the catch? Part II: OK, I'm convinced. Now what? 5. Start downloading (Raise your hand now if you've never burned an ISO disk image or installed Linux). 6. Get a computer (It's OK to be cheap - you wouldn't be reading this book if you weren't). 7. Installing Untangle(R). 8. Networking 101 (You might need to buy some more stuff here). Part III: So about this so-called "Server"... How do I protect my network? 9. What happens in the box? 10. Included software. 11. Optional software. 12. The user interface. 13. You don't have to be sitting in front of your new computer: remote administration for fun and profit. 14. The firewall. 15. The content filter. 16. The anti-malware. 17. The everything else. 18. Advanced topics. Part IV: I don't think this is enough for me - What's this "scalability" of which you speak? 19. Adding paid features to your box. 20. Bigger box? Bigger network? Or both? 21. When it's time to move to Untangle(R) hardware, pay for support, and give your first box to your grandmother. 22. When it's time to look beyond Untangle(R) . Appendix A: Repurposing a computer (minimum requirements, what you'll need, and what to do). Appendix B: Building your own computer (3 kits for 3 different use cases).
Keywords: Internet -- Security measures; Computer networks -- Security measures